2013
DOI: 10.1038/nature11993
|View full text |Cite
|
Sign up to set email alerts
|

Natural RNA circles function as efficient microRNA sponges

Abstract: MicroRNAs (miRNAs) are important post-transcriptional regulators of gene expression that act by direct base pairing to target sites within untranslated regions of messenger RNAs. Recently, miRNA activity has been shown to be affected by the presence of miRNA sponge transcripts, the so-called competing endogenous RNA in humans and target mimicry in plants. We previously identified a highly expressed circular RNA (circRNA) in human and mouse brain. Here we show that this circRNA acts as a miR-7 sponge; we term t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

71
6,569
4
26

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 6,564 publications
(6,860 citation statements)
references
References 26 publications
71
6,569
4
26
Order By: Relevance
“…Hence, circRNAs were more likely to be implicated within the mechanisms that gave rise to dysfunctional bioactivities, such as the onset and aggravation of cancers. For instance, ciRS‐7, the natural antisense transcript of cerebellar degeneration‐associated protein 1 (CRD1), contained approximately 70 MREs of miR‐7 24, 32, 36. Its high expression within cytoplasms could effectively lower miR‐7 activity through binding to it, thereby down‐regulating the expressions of insulin‐like growth factor‐1 receptor (IGF1R), epidermal growth factor receptor (EGFR) and focal adhesion kinase (FAK) 37, 38, 39…”
Section: Discussionmentioning
confidence: 99%
“…Hence, circRNAs were more likely to be implicated within the mechanisms that gave rise to dysfunctional bioactivities, such as the onset and aggravation of cancers. For instance, ciRS‐7, the natural antisense transcript of cerebellar degeneration‐associated protein 1 (CRD1), contained approximately 70 MREs of miR‐7 24, 32, 36. Its high expression within cytoplasms could effectively lower miR‐7 activity through binding to it, thereby down‐regulating the expressions of insulin‐like growth factor‐1 receptor (IGF1R), epidermal growth factor receptor (EGFR) and focal adhesion kinase (FAK) 37, 38, 39…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that circRNAs could function as miRNA ‘sponges’, and thus naturally sequester or competitively suppress the activity of target miRNA 35. To investigate the function of hsa_circ_0044235, the potential miRNA targets of hsa_circ_0044235 were predicted by using Arraystar's miRNA target prediction software.…”
Section: Discussionmentioning
confidence: 99%
“…A circRNA sponge for miR‐7 (ciRS‐7) has been of particular interest after Hansen et al. 129 found that ciRS‐7 and miR‐7 were coexpressed in the mouse brain. ciRS‐7 contains more than 70 conserved miRNA target sites and strongly suppresses miR‐7 activity, resulting in increased levels of miR‐7 targets.…”
Section: Introductionmentioning
confidence: 98%